CDL-CQI Day 2.0 for PKA UiTMCPP - Hashim, Khairul Afinawati; Muhammad Ali, Khairul Ammar; Ahmad, Hazrina; Wahid, Norlizan; Ruslan, Amir Khomeiny; Abdul Karim, Nurulzatushima; Mohamad Nor, Md Rasul (Unit Penerbitan FKAPP, 2025)
On 7th October 2024, CDL-CQI Day 2.0 was successfully organized by the Civil Engineering Centre (PKA) of UiTM Cawangan Pulau Pinang (UiTMCPP). The event saw the active participation of all lecturers from the Master’s program (CEEC707/708), Bachelor’s Degree program (CEEC221/223), and Diploma program (CEEC110). The primary objective was to enhance curriculum quality and to review the achievement of Program Outcomes (PO) for each course offered during the March 2024 – August 2024 semester (20242). Event Agenda: Opening and Outcome Presentation: The event commenced at 9:00 AM with a detailed presentation by the OBE Unit of PKA UiTMCPP on the analysis of PO achievements for the Mac 2024 - August 2024 Semester (20242). The presentation focused on the analysis results highlighted the performance and achievement of various program outcomes and provided insights into areas requiring improvements based on student performances. CQI Division Meetings: Following the presentation, the event continued with Continuous Quality Improvement (CQI) meetings, organized according to the four divisions within the faculty; STRUCM, GEOTREN, CEPM, and WRES. These meetings aimed to facilitate focused discussions tailored to the specific courses under each division. Lecturers engaged in collaborative dialogue to enhance teaching methodologies, refine assessment strategies, and improve overall course content. The goal was to ensure stronger alignment with program outcomes and accreditation standards.